2020
DOI: 10.1016/j.nonrwa.2019.103072
|View full text |Cite
|
Sign up to set email alerts
|

Eco-epidemiological model with fatal disease in the prey

Abstract: We investigate a model consisting of a predator population and both susceptible and infected prey populations. The predator can feed on either prey species but instead of choosing individuals at random the predator feeds preferentially on the most abundant prey species. Morespecifically we assume that the likelihood of a predator catching a susceptible prey or an infected prey is proportional to the numbersof these two different types of prey species. This phenomenon, involving changing preference from suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Eco-epidemiology is the combination of two distinct fields: ecology and epidemiology. Prior to 1979, 1,2 researchers worked in these fields independently. At first, Anderson and May 3 developed an eco-epidemiological model containing an infectious disease in the prey population.…”
Section: Introductionmentioning
confidence: 99%
“…Eco-epidemiology is the combination of two distinct fields: ecology and epidemiology. Prior to 1979, 1,2 researchers worked in these fields independently. At first, Anderson and May 3 developed an eco-epidemiological model containing an infectious disease in the prey population.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally ecology and epidemiology are two different branches in mathematical biology until Anderson and May 1 intermixed them, creating a new field of research in 1986, which is now known as the eco-epidemiology. Since then many researchers [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] have made significant contributions to this area. For example, Hadeler and Freedman 11 constructed a deterministic eco-epidemiological model where both prey and predator populations suffer from parasitism, and pointed out that the endemic thresholds are different with the traditional equilibrium-based basic reproductive number.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson and May [9] were the first to combine the two sciences and develop a predator-prey model with population illness. Many publications [10][11][12][13][14], Wang et al [15] examined numerous predator-prey models in the presence of infection in the system, and it was found that the illness is propagated by either prey or predator, or both prey and predator. The infectious illness divides prey-predator models into three categories.…”
Section: Introductionmentioning
confidence: 99%